Children’s education in Belo Horizonte in the COVID-19 pandemic context (Olhar de Professor, 2021)
The interruption of the school activities due to the pandemic caused by the COVID-19 resulted in many doubts regarding the 2020 school calendar. This paper analyzes the challenges and possibilities faced by institutions of the Municipal Education System of Belo Horizonte in relation to the legal determinations and the actions that guarantee children’s rights and the quality of the children’s education. The investigation, carried out through document analysis, seeks to contribute to the discussions about the dilemmas faced by children’s education in such context. The data collected suggest that the pandemic situation cannot override the guarantee of the right to the education of all children, considering the specificities of this age group teaching-learning process, as well as the social vulnerability of several families and the increase in social inequality.
Keywords: Children’s education. Municipal Education System of Belo Horizonte. COVID-19.